Liber de perfectione spiritualis vitae. Context și text (Verbum. Revista de teologie catolică, 2025)
The paper aims to present the opuscule Liber de perfectione spiritualis vitae on the occasion of the 800th anniversary of the author’s birth, given its recognized status as a classic work in the field of ascetic and mystical theology which offers a complete explanation of the higher Christian life. In the form of a sketch subsumed rather to the history of ideas, the paper includes a contextualization of the opus emergence, an outlining of its ideational chain and a specification of its role in drafting II-II of the Summa Theologiae.
Keywords: Thomas Aquinas; mendicant orders; spiritual perfection; state of perfection; poverty; charity